Putting 3D printing to good use—Additive Manufacturing and the Sustainable Development Goals - Muth, Jonathan; Klunker, Andre; Völlmecke, Christina (Frontiers in Sustainability, 2023)
Additive Manufacturing (AM), often referred to as 3D printing, is expected to have a high impact on the industry as well as on society. The inherent characteristics of AM make it possible to help solving global challenges, which can be examined by reference to the 17 Sustainable Development Goals (SDGs) of the United Nations. This is the first paper that examines the connection of AM and the 17 SDGs through a literature review. In this work, it is outlined which SDGs have a high, moderate or low potential to be fostered by AM. The SDGs are introduced and corresponding studies relevant to the respective SDG are presented. It is found that five out of 17 SDGs have high potential to be fostered by AM. These are SDG 1 (No poverty), SDG 3 (Good Health and Well-Being), SDG 4 (Quality Education), SDG 9 (Industry, Innovation, and Infrastructure), and SDG 12 (Responsible Consumption and Production). Furthermore, two SDGs have been identified that have moderate potential to be fostered by AM. These are SDG 7 (Affordable and Clean Energy) and SDG 10 (Reduced Inequalities).